Restoring Sight and Sound to the Algerian Woman: A Postcolonial Reading of Djebar’s novels - Al-Sudeary, Mashael A. (Mediterranean Journal of Social Sciences, 2012)
Known as Algeria’s most prominent woman novelist, Assia Djebar has successfully brought to the forefront issues of a feministnature all the while keeping her texts immersed within the discourse of nationalism. Djebar’s novels exhibit a multitude of femalepersonalities and experiences that defeat all attempts at fixating women into objects of textual representation. This paper aims atpresenting Djebar’s novels as counter narratives to the phallocentric constructions of the female figure as lack and Orientalistimplications of the feminine as marginal and inconsequential through the use of feminist and postcolonial approaches. By analyzing themulti-faceted accounts of women in Fantasia and Women of Algiers in Their Apartment, this paper seeks to replace old notions of astagnant female subject with one where women are vibrant figures of resistance, agency and change. It is mainly through the languageof the body as exemplified in the sound, gesture and ‘gaze’ that Djebar gives women a chance to be ‘visible,’ to represent themselvesand to speak with a voice that is unique and singular in its diversity from the norm, yet plural and multi-dimensional in its functionality androle.